2022
DOI: 10.1051/0004-6361/202142048
|View full text |Cite
|
Sign up to set email alerts
|

Radio footprints of a minor merger in the Shapley Supercluster: From supercluster down to galactic scales

Abstract: Context. The Shapley Supercluster (⟨z⟩≈0.048) contains several tens of gravitationally bound clusters and groups, making it an ideal subject for radio studies of cluster mergers. Aims. We used new high sensitivity radio observations to investigate the less energetic events of mass assembly in the Shapley Supercluster from supercluster down to galactic scales. Methods. We created total intensity images of the full region between A3558 and A3562, from ∼230 to ∼1650 MHz, using ASKAP, MeerKAT and the GMRT, with se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 112 publications
1
23
0
Order By: Relevance
“…At the center of the diffuse source region, there is a bright transverse bar. Such a bar has been detected in other bent tails (e.g., in A2443, Clarke et al 2013; and recently in the Shapley supercluster, Venturi et al 2022) and is predicted by simulations of interacting AGN tails and shocks (Nolting et al 2019). The length of this source, measured from the relic's edge down to the endpoints of the jets, is 10′, corresponding to 280 kpc at the Coma redshift.…”
Section: The Nat-relic Connectionmentioning
confidence: 60%
“…At the center of the diffuse source region, there is a bright transverse bar. Such a bar has been detected in other bent tails (e.g., in A2443, Clarke et al 2013; and recently in the Shapley supercluster, Venturi et al 2022) and is predicted by simulations of interacting AGN tails and shocks (Nolting et al 2019). The length of this source, measured from the relic's edge down to the endpoints of the jets, is 10′, corresponding to 280 kpc at the Coma redshift.…”
Section: The Nat-relic Connectionmentioning
confidence: 60%
“…However, new and highly sensitive low-frequency radio observations have revealed that the picture is much more complex, and other types of diffuse source (many of which do not fit our taxonomy) have been detected in recent years (e.g. Govoni et al 2019;Botteon et al 2020a,c;Ignesti et al 2020b;Hodgson et al 2021;Knowles et al 2022;Venturi et al 2022). The extremely large spatial scale of these sources, combined with the short lifetime of the relativistic electrons generating the synchrotron emission (𝜏 10 8 yr) implies in-situ acceleration by physical processes in the ICM.…”
Section: Introductionmentioning
confidence: 88%
“…With this large field of view (FOV), operating at low frequencies, and with baselines in the range 22 m and 6 km (providing sensitivity to radio emission on a wide range of angular scales), ASKAP is ideally suited to observations of low surface brightness diffuse radio 1 See https://www.narrabri.atnf.csiro.au/people/ste616/ beamshapes/beamshape_16cm.html for details of the ATCA 16 cm band beam model. sources typically found in many clusters of galaxies (HyeongHan et al 2020;Wilber et al 2020;Brüggen et al 2021;Di Mascolo et al 2021;Duchesne et al 2021a,c;Venturi et al 2022).…”
Section: Australian Square Kilometre Array Pathfindermentioning
confidence: 99%
“…Ultimately, the seed electrons upon which the reacceleration operates likely come from current or past AGN activity. Whether we can link specific filamentary structures to individual radio galaxies (as in cases where bars directly cross a tailed radio galaxy; Venturi et al 2022;Lame'e 2017;Botteon et al 2020) or where they appear to be the remnants of a dissipating lobe (Brienza et al 2022), or whether multiple AGN contribute to a mixed-background seed population, or whether both play a role, are major open issues.…”
Section: Icm Radio Features-the Emergence Of Filamentsmentioning
confidence: 99%